Initial training of nurses on the theme sexual and reproductive health: integrative review (Research, Society and Development, 2021)
The issues involving sexual and reproductive health are little or even not addressed by the fact that health professionals report difficulties in addressing this theme and, in addition to the discomfort in talking about sexuality or the sexual health of their patients, many of them do not feel prepared to exercise this care. This integrative review is a clipping of a dissertation. It is a systematized reflection on the development of strategies of articulation between the world of work, learning and society, based on the recognition of advances, weaknesses and strengths of the current model of health care having as its central axis principles of the SUS and the need for innovation of health practices and training. The objective is to characterize research that addresses the theme of sexual and reproductive health and that relates to the initial training of nurses. It is necessary to encourage research and applicability on sexual and reproductive health, especially with the updating of the nomenclature and the purpose in what the term means guaranteeing the dignity and sexual and reproductive rights of the population. It was possible to conclude that it is derisory the amount of articles that contemplate the termology sexual and reproductive health, making clear the embezzlement in this subject that is so relevant to Public Health. Even so, the publications relevant to the theme are predominantly research aimed at health professionals and/or the population.